Internal Audit and Sustainable Quality Assurance Practices in Zimbabwean Tertiary Institutions: A Literature Perspective - Pinias, Chikuvadze; Munyaradzi, Chidarikire (Global Journal of Educational Studies, 2024)
In the recent years the issue of quality of service delivery in Zimbabwean tertiary institutions has been at the centre of discussion at different fora. It is against this background that this paper sought to explore the role of internal audit in fostering sustainable quality assurance practices in Zimbabwean tertiary institutions. Thus, the discussion on interaction between internal audit with the view to create a sustainable quality assurance culture in tertiary institutions was viewed through a lens comprised the agency, and stakeholders theories. The methodology was qualitative in nature, grounded in content analysis, and interpretation with the view to provide a rich and thick inquiry into the issue. Hence, from the discussion it was noted that in tertiary education, and training, the production of goods, and services involves the interaction of mutually exclusive facets such as institutional management, resource mobilization, teaching-learning, and monitoring practices. This discussion came to a conclusion that the interaction of different facets of tertiary institutions based on control, compliance, accountability, and transparency thereby creating sustainable quality assurance practices that are vital in enhancing the right to use, and the quality of teaching-learning in tertiary institutions. Researchers recommends for an improvement of the existing quality assurance in teaching-learning, as a way to guarantee quality culture in tertiary institutions.